Correlation analysis of the serum CCR5 and LXA4 levels with airway remodeling in bronchial asthma patients and nursing summary: Serum CCR5 and LXA4 levels with airway remodeling in bronchial asthma - Huang, Haiyue; Luo, Ruirui; Yang, Xuan; Wu, Zhigang; Ding, Zhongxi (Journal of Medical Biochemistry, 2026)
[Objective] To analyze the expression levels of serum chemokine receptor 5 (CCR5) and lipoxin A4 (LXA4) in patients with bronchial asthma and their correlations with immune dysfunction and airway remodeling. [Methods] According to the severity of the disease, 240 patients with bronchial asthma admitted to our hospital from January 2023 to May 2025 were divided into mild to moderate asthma groups (n=180) and severe asthma groups (n=60). As the control group, 150 more healthy people who were admitted for a physical examination during that time were chosen. The serum CCR5 and LXA4 levels and immune function indicators (CD3+, CD4+, CD8+, and CD4+/CD8+) of each group were detected, and the airway remodeling indicators [airway lumen area (LA), airway wall area (WA) and total airway area (TA)] of the right upper lobe tip segment were examined via CT. The correlations between the serum CCR5 and LXA4 levels and immune dysfunction as well as airway remodeling were analyzed via a bivariate Spearman correlation test, and a multivariate logistic model was established to analyze the independent risk factors influencing the serum CCR5 and LXA4 levels in patients with bronchial asthma. [Results] Compared to the mild to moderate group, the severe group had greater serum levels of LXA4 and CCR5. Serum CCR5 was higher in the severe group than in the mild to moderate group, and LXA4 was lower in the severe group than in the mild to moderate group. There were statistically significant differences (P<0.05). Serum CD8+ T cell levels were higher than in the control group, whereas CD3+, CD4+, and CD4+/CD8+ T cell levels were lower in the mild to moderate and severe groups. Furthermore, the severe group had lower levels of CD3+, CD4+, and CD4+/CD8+ T cells than the mild to moderate group, whereas the mild to moderate group had greater levels of CD8+ T cells. The mild to moderate group of patients and the severe group of patients had lower levels of LA, WA, and TA in the right superior lobe apex segment than the control group, and patients in the severe group had lower levels of these three parameters than those in the mild to moderate group. There was a negative connection between serum CCR5 and LXA4 and CD3+, CD4+, and CD4+/CD8+ (P<0.05) and a positive correlation with CD8+, LA, WA, and TA. Multivariate logistic regression analysis revealed that disease severity, CD3+, CD4+, CD8+, CD4+/CD8+, LA, WA, and TA were independent risk factors for increased serum CCR5 and LXA4 in patients with bronchial asthma (P<0.05). [Conclusion] Serum CCR5 and LXA4 are closely related to the severity of bronchial asthma, immune dysfunction and airway remodeling.